2022
DOI: 10.1186/s12882-022-02858-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic obesity phenotypes and chronic kidney disease: a cross-sectional study from the RaNCD cohort study

Abstract: Background Investigating the effect of metabolic disorders on chronic kidney disease (CKD) in the presence or the absence of obesity is of great importance. This study aimed to examine the independent and joint relationships of obesity and metabolic syndrome (MetS) with CKD.  Methods  The present study was performed on 9,762 participants from the baseline phase of the Ravansar non- communicable diseases (RaNCD) study. Thereafter, the CKD was estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Metabolic and lifestyle risk factors are the most common causes of NCDs. Previous studies have shown that the prevalence of some NCDs, such as cardiovascular disease and chronic kidney disease, is higher in individuals with MUOW and MUNW phenotypes than in MHNW individuals [ 7 , 42 ]. Therefore, preventing shifting from a metabolically healthy status to MU status by dietary and lifestyle modifications can be beneficial in reducing the incidence of NCDs and correlated complications.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic and lifestyle risk factors are the most common causes of NCDs. Previous studies have shown that the prevalence of some NCDs, such as cardiovascular disease and chronic kidney disease, is higher in individuals with MUOW and MUNW phenotypes than in MHNW individuals [ 7 , 42 ]. Therefore, preventing shifting from a metabolically healthy status to MU status by dietary and lifestyle modifications can be beneficial in reducing the incidence of NCDs and correlated complications.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of CKD rises when patients with BMI ≥ 30 develop metabolic abnormalities and progress from metabolically healthy to unhealthy obesity [169][170][171][172]. Obesity is an independent risk factor for ESRD with a relative risk of 3.57 when BMI is ≥30 and 7.07 when BMI is ≥40 compared to when BMI is ≤25 [173].…”
Section: Obesitymentioning
confidence: 99%
“…In addition, obesity-associated local and systemic inflammation, insulin resistance, fibrogenesis, and gut microbiota dysbiosis are also associated with CKD development and progression [ 20 , 21 , 22 ]. Overweight and obese persons with metabolic disorders are more likely to develop CKD [ 23 ]. Thus, body weight control and a healthy diet are recommended for obese people.…”
Section: Obesity Its Comorbidities and Associated Factorsmentioning
confidence: 99%